2011
DOI: 10.1007/s13157-011-0247-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Hydrogeomorphic Wetland Inventory: Reclassifying National Wetlands Inventory Polygons in Geographic Information Systems

Abstract: The National Wetlands Inventory (NWI) is the most extensive inventory of wetland resources in the U.S., but it has limited ability to contribute to characterizations of wetland functions. We provide a methodology for reclassifying NWI polygons into Hydrogeomorphic (HGM) classes to facilitate monitoring wetland functions. We conducted this reclassification using spatial and attribute queries within Geographic Information Systems (GIS) for wetlands in central Oklahoma. Once classified, 149 randomly selected wetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Crane (2014) similarly concluded that buffer metrics in the USA-RAM did not reliably predict vegetation diversity for Oklahoma depressional wetlands, and Bried et al (2014) showed mismatches between the USA-RAM buffer assessment and vegetation-based wetland quality classes in Oklahoma. Wetland assessment and classification in general appears to be challenging across Oklahoma due to a high degree of environmental and climatic variability (Hoagland 2000;Dvorett et al 2012Dvorett et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crane (2014) similarly concluded that buffer metrics in the USA-RAM did not reliably predict vegetation diversity for Oklahoma depressional wetlands, and Bried et al (2014) showed mismatches between the USA-RAM buffer assessment and vegetation-based wetland quality classes in Oklahoma. Wetland assessment and classification in general appears to be challenging across Oklahoma due to a high degree of environmental and climatic variability (Hoagland 2000;Dvorett et al 2012Dvorett et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the depressional HGM class versus an Bother HGM^category containing riverine, fringe, and seep wetlands, but the model incorporating this effect received the lowest empirical support. Regional HGM subclasses offer better ecological resolution but were not used due to sample size limitations and the difficulty in characterizing and ascribing wetlands to subclasses in Oklahoma (Dvorett et al 2012). High climatic variability may also pose a challenge for wetland assessments in this region (Dvorett et al 2013), and we did not account (explicitly) for the wide range of precipitation across Oklahoma (Hoagland 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Because the developers of each classification essentially made the class assignments, errors of misclassification are negligible. Although mapping errors are possible in NWI (Dvorett et al 2012), we assigned classes based on the conditions found on the field visit.…”
Section: Cook Inlet Classification Systemmentioning
confidence: 99%
“…(1) a reference wetlands guide assembled by the Oklahoma Conservation Commission (Henley and Harrison 2000), (2) past wetland vegetation inventories by the Oklahoma Biological Survey, (3) past wetland studies by Oklahoma State University (Hartzell et al 2007;Dvorett et al 2012;unpubl. data), and (4) exhaustive field searches in 30 public, protected areas.…”
Section: Site Selectionmentioning
confidence: 99%
“…1) but due to sample size limitations the ecoregions were grouped into general forest and prairie regions (see Appendix 1). Following Brinson (1993) and Dvorett et al (2012), most sites were assigned to riverine or depressional hydrogeomorphic (HGM) classes and a few to seep and fringe classes (Appendix 1). We did not use HGM subclasses for this study due to sample size limitations and because many subclass categorizations are uncertain in this region (Dvorett et al 2012).…”
Section: Site Selectionmentioning
confidence: 99%